Peran Taman Bacaan Masyarakat dalam Mengembangkan Kreativitas Anak dan Remaja - Tania Sapitri; Seli Vebrianti; Dede Rahma Monika; Fadilah Nurul Huda; Regina Rostarina Julyanti; Ahmad Hamdan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the role of the Pustaka Prima Community Reading Park (TBM) as an alternative learning space that provides non-formal educational experiences for children and adolescents, especially in communities with limited access to educational facilities. Through a descriptive qualitative approach, this study explores the contribution of TBM in developing creativity, literacy skills, self-expression, and independent learning of participants. Data was collected through participant observations, semi-structured interviews with managers and participants, and documentation of program activities. The results of the study show that TBM Pustaka Prima plays a significant role in strengthening cognitive, social, and emotional development through various activities such as reading literacy, storytelling, basic entrepreneurship training, and other creative activities. These programs have been proven to increase reading motivation, the ability to understand texts, confidence in communication, technology awareness, and the ability to innovate. An inclusive and collaborative learning environment allows participants to explore knowledge, work together, and optimize their potential. These findings confirm that TBM not only functions as a provider of reading materials, but also as a community-based education center that provides meaningful learning experiences outside the formal education system. The implications of the research emphasize the importance of strengthening collaboration, developing sustainable programs, and improving resources and infrastructure to maximize the role of TBM in community empowerment.